Effective first-person biblical preaching : the steps from text to narrative sermon - Edwards, J. Kent, 1958- (Grand Rapids, Mich. : Zondervan, 2005)
"A practical resource to help students and pastors understand why and how first-person sermons can be preached with biblical integrity. Includes extensive examples and worksheets"--Provided by publisher.
Foreword / by Haddon W. Robinson -- Introduction : what I have learned along the way -- Why preach expository first-person sermons? -- Beginning to use the narrative exegetical key -- Step one : adjust your interpretive paradigm -- Step two : understand the larger context of the story your want to preach -- Determining the story's structure -- Step three : determine the structure of your story -- What comes next? -- Step four : analyze the characters -- Step five : discover the setting of the story -- Step six : state the "big idea" of the narrative -- Step seven : double-check your big idea -- Step eight : make the application -- Taking the first steps in the homiletical task -- Step one : select an appropriate text -- Step two : ensure that you have identified the big idea of your narrative -- Step three : develop the protagonist for your story -- Step four : create your antagonist -- Completing the homiletical task -- Step five : set the story -- Step six : plot the action -- Step seven : determine the perspective -- Step eight : create your lesser characters -- Step nine : write the manuscript -- Step ten : decide about props -- Step eleven : refine your manuscript -- Step twelve : block your sermon -- Step thirteen : rehearse your sermon -- Step fourteen : decide about costuming -- Step fifteen : deliver your sermon -- Practical questions about first person preaching -- Narrative alternatives to first person preaching.
"Includes CD-ROM with video demonstration"--Cover.
Includes bibliographical references and indexes.
System requirements for accompanying disc: Windows: Pentium II or III; 128MB RAM; Windows 98, 2000, XP; Microsoft Internet Explorer 5.01 (sp2), 5.5 (sp2) or 6 (sp1); monitor (800 x 600 minimum screen resolution); Macintosh: Power Macintosh G3; 128MB RAM; OS 9.2, 10.1.5, 10.2.6, 10.3; Internet Explorer 5.2 or later, Netscape 7.1, Safari 1.1; monitor (800 x 600 minimum screen resolution)
Keywords: Narrative preaching